Detection of Amino Acids from The Stem Bark of Juglans regia - A. Kale, Asha; A. Gaikwad, Sucheta; S. Mundhe, Kavita; R. Deshpande, Nirmala; P. Salvekar, Jyoti (Asian Journal of Chemistry, 2010)
Family Juglandaceae includes a valuable, medicinally useful species Juglans regia, growing in the forests of Himalayas in India. The root, stem, bark, leaves, seeds, cotyledons and seed oil are used to treat a variety of health complaints. Amino acids play an important role in plant biogenesis. Detection of amino acids was carried out on the stem bark of the species by paper chromatographic method using different mobile phases. Results show the presence of leucine, tyrosine, proline, methionine, ornithine, alanine, etc. in the different solvent systems.